Challenges and Opportunities in Developing Local Wisdom-Based Science Learning Modules: A Systematic Literature Review - Fandi, Real; Nurrochman, Sabar; Adumiranti, Yuninda; Niyamae, Ade Noorliza (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2025)
: The development of science learning modules based on local wisdom has become one of the innovative strategies to enhance students' science literacy and preserve cultural values. However, in its implementation, various challenges are still encountered, such as limited educational resources, lack of integration between modern science and local wisdom, and minimal community participation in the development process. This study uses the Systematic Literature Review (SLR) method with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach t o ensure transparency and traceability in the literature selection process. From the screening results using the PRISMA diagram, four main articles that met the inclusion and exclusion criteria were obtained. The analysis shows that the development of digital technology, supportive educational policies, and interdisciplinary collaboration are the main opportunities in the development of this module. Additionally, recent research trends show a significant increase in the use of interactive multimedia and context-based learning approaches. The results of this research provide insights for educators, researchers, and policymakers in developing more effective and innovative science learning modules based on local wisdom